(untitled) (Sustainability in Debate, 2011)
IThis research investigated the effects of the interdependence between political institutions and development models in the performance of environmental policies in Brazil. The central hypothesis of this work is that given the interdependence between the organizations responsible for environmental policies and development patterns somewhat responsive to environmental complexity, there is a dispersion of decision-making model for encouraging the development of high-carbon. In addition to literature review in Ecological Economics and Public Policy, were put into operation (1) an analysis of brazilian political-institutional design, and (2) the public expenditure framework of the Brazilian federal government with the environment. Two results were observed: first) the design and the powers of the institutions responsible for policy formulation and implementation of public policies interfere with the efficiency of environmental policies; second) the higher the institutional openness, the greater the tendency of decision-making paralysis in the formulation and implementation of environmental public policies.